Existence Results for Fractional Differential Equations with Multistrip Riemann–Stieltjes Integral Boundary Conditions. (24th April 2018) - Lv, Tongling; Pang, Huihui; Cao, Limei
Abstract : This paper is concerned with the existence and multiplicity of the positive solutions for a fractional boundary value problem with multistrip Riemann–Stieltjes integral boundary conditions. Our results are based on the Leggett–Williams fixed point theorem. In the end, two examples are worked out to illustrate our main work.